Robust Cooperative Controller for Output Regulation in Multi- Robot Systems - Rostami Kia, Sajad; Akbarimajd, Adel (International Journal of Integrated Engineering, 2016)
In this paper a robust cooperative multi-agent controller is designed for a linear uncertain multi-robot system with a nonlinear exosystem. Multi-robot system is divided into two subsystems; the first group of subsystems can be associated with the leader while the second group has no leader. Assuming that all agents are similar and have the same dynamics and decentralized control, state and output feedback control rules are proposed. Multi-robot system with nonlinear exosystem is simulated in MATLAB and tracking performances with state and output feedback controllers are investigated.